PENGEMBANGAN TRADISI KEILMUAN BERBASIS KEPEMIMPINAN KIAI - Arshinta Zahrotul Laila; Rido Kurnianto; Aldo Redho Syam (TARBAWI:Journal on Islamic Education, 2021)
The kiai's leadership strategy has an important role in developing a scientific culture in pesantren. The existence of this scientific culture can also be seen from the educational orientation organized by the Badii'usy Syamsi Pucanganom Madiun Modern Islamic Boarding School. Through the application of the right leadership strategy, it is believed to be able to maintain the existence of pesantren as a tafaquh fidin institution and maintain the scientific culture of pesantren. This study describes the process of building a scientific tradition from the perspective of the leadership strategy of kiai Ponpes Badii'usy Syamsi and the supporting and inhibiting factors. This research uses a case study type approach. The results showed that 1); the process of scientific development at the Modern Badii'usy Syamsi Islamic Boarding School is carried out by carrying out co-curricular, extra-curricular, and intra-curricular activities; 2). The scientific tradition is developed through four strategies, namely; barter (exchange), build (build), bind (bind), tie (bond); 3). The factors encountered at the beginning of the pioneering pesantren were difficulties in providing books for santri, not having formal education, salafi education models that were not accepted by the community, lack of human resources to teach in pesantren, supporters consisting of family environment, colleagues, motivation and the principle of unwavering coordination, as well as the pesantren cadres who have started well at the Badii'usy Syamsi Modern Islamic Boarding School.